The impact of organizational support on three dimensions of achievement motivation in leadership role of extension agents in Iran - Karami, Roya; Ismail, Maimunah; Badsar, Mohammad; Omar, Zaharah; Abdul Wahat, Nor Wahiza (2011)
The study aims to assess the relationships of organizational work and non work supports with three dimensions of achievement motivation in leadership role. The study data were collected from 303 extension agents from the Ministry of Agriculture in Iran. The data were analyzed using AMOS software. The results showed that organizational work supports significantly related to aspiration and mastery dimensions of achievement motivation while organizational non work supports significantly related to aspiration and salience dimensions of achievement motivation. The study is useful for extension organizations to convey the favorable treatment including work and non work support to motivate the agents to achieve leadership role. The HRD implications are discussed.